TINJAUAN SISTEMATIS TERHADAP FAKTOR-FAKTOR YANG MEMPENGARUHI KECENDERUNGAN BERHUTANG - Nisa, Khairun; Hamidah, Hamidah; Ketut Agung Ulupui, I Gusti (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study systematically reviews behavioral factors contributing to indebtedness, analyzing 60 articles from Scopus, Science Direct, Google Scholar, and Web of Science databases using the PRISMA framework. Key findings identify low financial literacy, materialism, negative emotions, risk perception, consumer behavior, and behavioral biases (such as overconfidence) as key drivers. Demographic and socioeconomic factors act as moderators, and over-indebtedness is negatively associated with health and well-being. It concludes that indebtedness is a complex interaction of cognitive, affective, and dispositional dimensions, and effective interventions must be multifaceted, encompassing education and mitigation of maladaptive behaviors for sustainable financial well-being.